A dimensão territorial da inovação e sustentabilidade no território de cachaça e dos derivados da cana – Litoral Norte do Rio Grande do Sul - Shana Sabbado Flores (Confins)
The paper aims to analyze the territory of "Cachaça and Sugarcane’s products", in Santo Antônio Patrulha, noticing factors that contribute to processes of innovation and sustainability in the territory. The city stands out for a different profile in one of the poorest regions of the state, and has GDP per capita almost twice the average of the Northern Coast. The insertion of sugarcane in the state took place in the eighteenth century, late compared to the rest of the country; a specificity of RS is the structure in small farms aimed at handmade producing of sugarcane based candies to supply the domestic market. From the nineteenth century the region is recognized as a sugarcane producer, in an industrial perspective. After successive crises, this territory has rescued some local characteristics and traditions, which have resulted, from the 80s, to candy factories based of brown sugar and molasses, and later, the “alambiques” (still), from the 90s. Thus, reinventing itself and using local resources and traditions, the sector ensured their continuity. The territory based innovation process was essential to ensure the sustainability of the territory to date. Today, the cluster is an institutionalized network, recognized and supported by public policies. The territorial-based innovation processes took place not only inside the companies, but also in its organization and relationship with the territory. Local factors linked to products and processes provide specific characteristics to the products, as well as the culture among the institutions and products of this territory also act in order to strengthen local identity. They are points of stability that allow reinterpretation and innovation, bringing proposals to better utilize the land resources and thus ensure its sustainability in broad.